Die Welt der New-Adult-Buchreihen: Erfolgsfaktoren eines wachsenden Büchergenres bei jungen Zielgruppen - Tanja Zweigle; Fabienne Ehrenfried (IU Internationale Hochschule, 2024)
The New Adult genre, as a subgenre of romance novels, is only a few years old, but it has become an indispensable part of the German book market for young female audiences. This study examined the success factors of New Adult book series to understand what exactly leads to the market success of this genre, particularly among young audiences, the Gen Z. It reveals what the readership values and how these factors influence loyalty to authors, publishers, and bookstores. To do this, 100 German-language New Adult book series were compared based on various action- and marketing-oriented criteria, followed by an online survey with 196 self-selected female New Adult readers. They were also asked about the relevance of these various criteria. It can be stated that marketing-oriented factors like book covers can trigger a purchase, but action-oriented factors like multilayered characters and sensitive, authentic treatment of profound topics emotionalize books to such an extent that emotional loyalty can be created, and readers want to read sequels. Promotional activities such as autograph campaigns can hold the established excitement on a high level. The proximity of authors and publishers to their readers, especially through social media, enables a fan loyalty and the mutual development of genre and target group.
Keywords: M31; 650; New-Adult-Genre; Bookfluencer; Buchreihen; Generation Z; Leseverhalten